Systematic Analysis of Scale Effects on Form Factor - Argyros, Minas (My University, 2023)
The purpose of the present master thesis is to investigate the difference between model scale and full scale form factor Computational Fluid Dynamics (CFD) computations, using a new established method. This method called the two-form factor method (or 2-k method) exposed in two recent research papers shows improvements in the accuracy of form factor estimation, providing consequently better results by applying the full scale process, especially in case of stern flow separation phenomena, such as bubble type flow separation and recirculation type flow separation. The present master thesis will investigate this form factor procedure using five benchmark hulls, as well as two commercial hulls being provided by the database of FORCE Technology with the aim of having better insights about the aforementioned investigated phenomena. First of all, Verification and Validation (V&V) of the CFD results is executed by comparing the CFD form factor results obtained with the available model scale experimental results. Furthermore, a systematic analysis of changing the scale factor of the test cases is applied in order the scale effects to be studied. Moreover, sensitivity analysis of different roughness heights is implemented so as the effect of the equally distributed roughness to be investigated in full scale CFD computations. All in all, implementing the systematic analysis in scale, roughness and draft variations, the results show that the two form factor method is considered an holistic and trustworthy method which can provide reliable prediction of form factor even for the case of intense turbulence phenomena in the wake of transom.
Keywords: CFD; Systematic analysis; Scale effects; Form factor; 2-k method